Ducted Fuel Injection: Experimental and numerical investigation on fuel spray characteristics, air/fuel mixing and soot mitigation potential. (1st April 2021) - Millo, F.; Piano, A.; Peiretti Paradisi, B.; Postrioti, L.; Pieracci, L.; Bianco, A.; Pesce, F.C.; Vassallo, A.
Highlights: Ducted Fuel Injection (DFI) enables for highly mixing controlled diesel combustion. DFI enhances air entrainment in the near-nozzle region and turbulence at duct exit. Remarkable droplet count reduction due to enhanced evaporation for DFI. Impressive soot reduction potential due to narrower equivalence ratio distribution. Abstract: Enhancing mixture preparation upstream of the premixed autoignition zone is a solution to reduce soot emission formation in compression ignition engines. With this aim, in recent years, Ducted Fuel Injection (DFI) concept has been developed: DFI is based on the idea of injecting the fuel spray through a small cylindrical pipe within the combustion chamber at a certain distance from the nozzle injector hole. Recent research studies have highlighted the high potential of this innovative concept for soot mitigation in both constant volume vessel and engine-like operating conditions. However, the mechanisms driving the soot reduction have not yet been fully understood. The aim of this research work is to further investigate the DFI concept, evaluating its impact on the spray characteristics, on the air/fuel mixing and, therefore, on the soot formation phenomena. Firstly, an experimental activity was carried out by means of a constant volume vessel test bench with optical accesses to compare the spray evolution and sizing with and without duct adoption, over a wide range of vessel thermodynamic conditions and injection pressures. After that, a simulation setup was defined in the commercially available 3D-CFD software CONVERGE reproducing the experimental test bench, calibrating and validating the spray model. Firstly, the spray model was calibrated and validated considering the same non-reacting conditions exploited in the experimental analysis. Then, the calibrated spray model was used as a virtual tool to investigate the air entrainment process. As a results, the DFI adoption increases the air entrainment in the near-nozzle region caused by the high velocity spray that generates a pumping effect at the duct inlet. Moreover, mixing process is also enhanced by the turbulence distribution at the duct exit resulting in a narrower distribution of equivalence ratio at the ignition. As a consequence of the more effective air entrainment and improved turbulent mixing, DFI remarkably mitigates soot emissions, with a reduction up to 80% with respect to free spray configuration in all tested operating conditions.